The power of digital medicine: A new era in healthcare - Ganesh, Sritheran Paneerselvam; Long, Chiau Ming * (InfoMed "Malaysia" Sdn Bhd, 2023)
Digital medicine refers to the use of digital technologies to enhance the delivery and effectiveness of medical care. It is a rapidly growing field that has the potential to revolutionize healthcare delivery and improve patient outcomes. It encompasses a range of technologies, including mobile apps, wearables, telemedicine, and artificial intelligence (AI). Digital medicine has the potential to revolutionize the way diagnosis, treatment, and disease management are made to improve patient outcomes.